Improving Student Learning Motivation in Islamic Education at SD Negeri 05 Sungai Bungin through the Cooperative Learning Model - Hendrika, Rafvi (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve students' learning motivation in Islamic education learning using the Cooperative Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to measure the improvement of student learning outcomes in Islamic education learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning using the Cooperative Learning Model can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 49.56%, the first cycle 70.47% and in the second cycle increased to 90.57%. Thus, the use of the Cooperative Learning Model can be used as an alternative to increase student activity in Islamic education learning in Islamic religious education learning.